The Divine Liturgy in the Wall Paintings of the 15th–16th Centuries in Macedonia - Onufrienko, Maksim O. (Actual Problems of Theory and History of Art, 2020)
The article examines the Divine Liturgy scenes in the wall paintings of the 15th–16th centuries in Macedonia. At this time, both iconographic versions of the Divine Liturgy plot, which developed in Byzantine art, were still used. Frequently these scenes are located in the dome or altar apse. Their inclusion in the wall decoration can be explained by the continuation of the usage of the Paleologan period schemes. Artists follow a single compositional scheme: angels-deacons and angels-priests march with the Holy Gifts to the altar, next to which there are two figures of Christ the High Priest. However, there are several examples of referring to the first half of the 14th-century schemes: Assumption Cathedral of Treskavac Monastery (1480s) and St. Panteleimon Church at Nerezi (second half of the 16th century). Also, there are two churches, which were influenced by the rare Byzantine compositions such as the drum painting of the Savior Church in Thessaloniki (mid-14th century) and the altar of St. Fanourios church in Valsamonero (15th century). There are the narthex frescoes of St. Nicholas church of the Toplici monastery (1534/1535) and St. Nicholas church in Zrze (mid-16th century). In the first case, the angelic Great Entrance procession was supplemented with the images of earthly deacons as well as Sts. Basil the Great and, presumably, John Chrysostom. The depiction of the holy hierarchs together with earthly clergy express the idea of the conciliar unity of the Church and convey the state of prayer of those in the church. In the second case, the Great Entrance motif is included in the Officiating Bishops scene, which resembles the altar program of St. Demetrius church of Markov Monastery. So, liturgical plots in Macedonian post-Byzantine art had some originality.
Keywords: Liturgical Plots; Divine Liturgy; Post Byzantine art; Macedonian art; Toplica Monastery; Treskavec Monastery